Spectator: Thoughts on the relationship of politics and the academy - Botha, M. Elaine (Koers, 1977)
“In the sphere of ultimate loyalties, universities share the confusion and unsettlement of the world at large. They have no agreed criteria by which to assess their policies, organization, teaching methods and the forms of communal life; they have not even fruitful disagreement. They tacitly refuse to take cognizance of really contentious and difficult issues. They label them ‘Dangerous, do not touch’, and thrust them out of sight. But that is a lazy and pusillanimous evasion of responsibility. They can give no light or guidance to a directionless world, so long as they are them selves directionless and are content to remain so.” (Sir Walter M oberly. 1949. The crisis in the university. Second impression.)